2019
DOI: 10.3390/brainsci9080182
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sickle Cell Disease Pain among Adolescent and Pediatric Patients

Abstract: Management of sickle cell pain in adolescent and pediatric patients is inadequate, and the employment of proper management guidelines and practices are highly variable among different regions and populations. APPT, the multidimensional adolescent pediatric pain tool, promotes optimal pain management and introduces best practical guidelines for pain management. The goal of this study is to assess pain and pain management among young patients diagnosed with sickle cell disease (SCD) by introducing the APPT as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
5
3
2
Order By: Relevance
“…Evaluation of the level of pain experienced by the participants showed that the majority experienced mild pain, while a few participants had severe pain. This result was not in agreement with the report of Abdo et al, in which most participants experienced severe to moderate pain, which could be attributed to the lack of self-care knowledge that could have helped in alleviating pain [38]. The reason for the low proportion of participants in this study with moderate/sever pain compared to the study by Abdo et al study might be that while their study was conducted among SCD patients in a secondary/tertiary level hospital, ours was conducted among patients attending a primary level of health care [38].…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Evaluation of the level of pain experienced by the participants showed that the majority experienced mild pain, while a few participants had severe pain. This result was not in agreement with the report of Abdo et al, in which most participants experienced severe to moderate pain, which could be attributed to the lack of self-care knowledge that could have helped in alleviating pain [38]. The reason for the low proportion of participants in this study with moderate/sever pain compared to the study by Abdo et al study might be that while their study was conducted among SCD patients in a secondary/tertiary level hospital, ours was conducted among patients attending a primary level of health care [38].…”
Section: Resultscontrasting
confidence: 99%
“…This result was not in agreement with the report of Abdo et al, in which most participants experienced severe to moderate pain, which could be attributed to the lack of self-care knowledge that could have helped in alleviating pain [38]. The reason for the low proportion of participants in this study with moderate/sever pain compared to the study by Abdo et al study might be that while their study was conducted among SCD patients in a secondary/tertiary level hospital, ours was conducted among patients attending a primary level of health care [38]. Usually, primary level health care involves uncomplicated simple cases, while complicated ones are referred to secondary/tertiary level health care facilities.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This research divides patients into subgroups to look at pain variability differently. 5 The authors might have examined intraindividual pain variability and subgroup membership by including these subgroup classifications. In 2019, the Pediatric Pain Screening Tool was used to assess chronic pain risk factors in sickle cell patients.…”
Section: E T T E R T O T H E E D I T O R Comment On: Intraindividual ...mentioning
confidence: 99%